1987
DOI: 10.1002/cne.902560111
|View full text |Cite
|
Sign up to set email alerts
|

Effects of corpus callosum section on functional compensation in the posteromedial lateral suprasylvian visual area after early visual cortex damage in cats

Abstract: A visual cortex lesion made in adult cats leads to a loss of direction selectivity and a loss of response to the ipsilateral eye among cells in posteromedial lateral suprasylvian (PMLS) cortex of cats. However, a visual cortex lesion made in young cats results in normal direction selectivity and normal ocular dominance in PMLS cortex. Thus cats with an early lesion demonstrate functional compensation in PMLS cortex. The present experiment determined whether the functional compensation depends upon an intact co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…receptive field properties that are indistinguishable from those in intact cats Tong, Kalil, & Spear, 1984;Tong, Spear, & Kalil, 1987). It is not yet clear, however, how the output from PMLS and related lateral cortical areas controls neurons in other brain areas, such as the superior colliculus and pretectum, which are involved in essential aspects of the spared visually guided behaviors described in the present article.…”
Section: Lateral Suprasylvian Cortexmentioning
confidence: 64%
See 1 more Smart Citation
“…receptive field properties that are indistinguishable from those in intact cats Tong, Kalil, & Spear, 1984;Tong, Spear, & Kalil, 1987). It is not yet clear, however, how the output from PMLS and related lateral cortical areas controls neurons in other brain areas, such as the superior colliculus and pretectum, which are involved in essential aspects of the spared visually guided behaviors described in the present article.…”
Section: Lateral Suprasylvian Cortexmentioning
confidence: 64%
“…Neurons in area PMLS depend upon inputs from area 17 and 18 for the generation of normal receptive field properties and several features of the receptive fields are eliminated when areas 17 and 18 are removed (Hubel & Wiesel, 1969; Spear & Baumann, 1979). However, when these same areas are removed before a kitten is between 12 and 18 weeks of age, area PMLS undergoes a physiological compensation and the majority of neurons have receptive field properties that are indistinguishable from those in intact cats (McCall, Tong, & Spear, 1988; Spear, Tong, & McCall, 1988; Tong, Kalil, & Spear, 1984; Tonk, Spear, & Kalil, 1987). It is not yet clear, however, how the output from PMLS and related lateral cortical areas controls neurons in other brain areas, such as the superior colliculus and pretectum, which are involved in essential aspects of the spared visually guided behaviors described in the present article.…”
Section: Discussionmentioning
confidence: 99%
“…First, this input is extensive in adult cats (Keller & Innocenti, 1981;Segraves & Rosenquist, 1982) and potentially even more widespread in kittens (Innocenti & Clarke, 1984). Second, callosal inputs are partly responsible for another form of binocular compensation in the LS visual area, one that follows neonatal damage to the striate cortex Tong et al, 1987). Third, in Siamese cats, in contrast to other areas of their visual cortex, a majority of neurons in area LS are binocular: a special feature that is mediated by callosal input (Marzi et al, 1980;Zeki & Fries, 1980).…”
Section: Anatomical Basismentioning
confidence: 99%
“…The idea that intact brain areas may reorganize their activity to compensate for other functionally impaired areas (e.g., because of cerebral lesions or degenerations) is not new. For example, back at the end of the last century, several papers by Spear, Tong, et al [100][101][102] reported that the posteromedial lateral suprasylvian (PMLS) visual cortical area in the cat showed physiological compensation after damage to hierarchically lower visual areas (Brodmann's 17, 18, and 19), provided that the damage occurred early in the animal's life. Even if such compensation could not completely overcome the deficits [101], PMLS neurons could develop the properties they would have had in the absence of brain damage.…”
Section: Neural Plasticity and Compensatory Mechanismsmentioning
confidence: 99%